Exploring Motivations for Domestic Violence by Women in Saudi Arabia - Khadhar, Fowzah (Journal of family violence, 2022)
Both women and men suffer from domestic violence around the world. While domestic violence against women has received considerable research attention, domestic violence against men has been under-studied, especially in the Kingdom of Saudi Arabia. The limited data available from the National Family Safety Registry of Saudi Arabia and the National Society for Human Rights suggest that female-perpetrated domestic violence has been increasing in Saudi Arabia. This research therefore aims to understand the reasons why women commit violence against men in Saudi Arabia. The study uses a qualitative research method, using data obtained through semi-structured interviews conducted at a women’s prison in Riyadh, Saudi Arabia, with 30 women who were incarcerated for committing violence against men. Thematic analysis shows that participants in this study committed their offence due to two main reasons: self-defense and emancipatory longing. While some participants reported being abused and mistreated, leading them to commit violence to protect themselves, others reported actively using violence against men out of frustration and a desire to be free from oppressive patriarchal practices. The study also provides evidence that institutions can act as spaces of freedom for women frustrated with patriarchal practices and wanting freedom from oppression. Patriarchal practices can be a source of great frustration for women and can motivate them to commit violence. The Saudi government has taken steps to address such practices; however, for effective change to occur there remains a need for change in the societal mindset about the role of women.